Nuclear myosin 1 activates p21 gene transcription in response to DNA damage through a chromatin-based mechanism - Venit, Tomas; Semesta, Khairunnisa; Farrukh, Sannia; Endara-Coll, Martin; Havalda, Robert; Hozak, Pavel; Percipalle, Piergiorgio (Communications biology, 2020)
Nuclear myosin 1 (NM1) has been implicated in key nuclear functions. Together with actin, it has been shown to initiate and regulate transcription, it is part of the chromatin remodeling complex B-WICH, and is responsible for rearrangements of chromosomal territories in response to external stimuli. Here we show that deletion of NM1 in mouse embryonic fibroblasts leads to chromatin and transcription dysregulation affecting the expression of DNA damage and cell cycle genes. NM1 KO cells exhibit increased DNA damage and changes in cell cycle progression, proliferation, and apoptosis, compatible with a phenotype resulting from impaired p53 signaling. We show that upon DNA damage, NM1 forms a complex with p53 and activates the expression of checkpoint regulator p21 (Cdkn1A) by PCAF and Set1 recruitment to its promoter for histone H3 acetylation and methylation. We propose a role for NM1 in the transcriptional response to DNA damage response and maintenance of genome stability.
Keywords: poškození DNA; histonlysin-N-methyltransferasa; Cell Line; Histone-Lysine N-Methyltransferase; Cell Nucleus; DNA Damage; Cell Proliferation; restrukturace chromatinu; Transcription, Genetic; epigeneze genetická; p300-CBP Transcription Factors; Myosin Type I; etoposid; buněčné jádro; nádorový supresorový protein p53; genetická transkripce; inhibitor p21 cyklin-dependentní kinasy; Animals; transkripční faktory p300-CBP; zvířata; Tumor Suppressor Protein p53; Cell Cycle; myši; buněčné linie; apoptóza; proliferace buněk; buněčný cyklus; Cyclin-Dependent Kinase Inhibitor p21; Mice; myosin typu I; Chromatin Assembly and Disassembly; Apoptosis; Etoposide; Epigenesis, Genetic